Legalitas sebagai Fondasi Keberlanjutan UMKM di Indramayu: Sosialisasi dan Pendampingan NIB Menggunakan OSS - Atmadja, Ferry Setyadi; Utari, Eka Dewi; Rabbaniyah, Lathiefah; Nida, Ria Rahma; Widarum, Chaerunisha Aila; Ayyun, Dinda Ramadhani Qurrota (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2025)
Obtaining legal business status is crucial to strengthening the foundation for the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Karangsong Village, Indramayu Regency, a coastal area. Through a collaborative partnership between the Faculty of Economics and Business at Universitas Negeri Jakarta and the Fisheries and Maritime Affairs Office of Indramayu, including the local government apparatus of Karangsong Village, this program provides comprehensive assistance to MSME actors in acquiring their Business Registration Numbers (NIB). Using systematic observation, in-depth data collection, direct guidance, and socialization throughout the NIB registration process, the program addresses the main challenges related to business legality. This intervention helps improve business legitimacy for MSMEs, operational compliance with government regulations, and access to broader market opportunities. The program affirms the important role of empowering business legality for MSMEs as the foundation for sustainable MSME growth and grassroots economic development.